Chitosan-Raloxifene nanoparticle containing doxorubicin as a new double-effect targeting vehicle for breast cancer therapy - Mohammadi, Zohreh (Daru, 2020)
BACKGROUND: treatment of breast cancer as one of the most common cancers in the world remains an important area of drug development based on nanoparticulate systems. Effective targeted therapy of affected cells based on ligand conjugate biocompatible polymeric nanoparticles is an attractive perspective in this context. OBJECTIVE: In this study, a novel double effect nanoparticle based on Chitosan-Raloxifene conjugate was prepared for adjuvant therapy (hormone and chemo therapy) and drug targeting to breast cancer cells via estrogen receptor (ER). METHODS: Chitosan-raloxifene conjugate was synthesized. Related nanoparticles containing doxorubicin (DOX) were prepared and characterized. Experimental design study was performed to determine the optimum levels of variables in the preparation of nanoparticle. Drug loading, release, nanoparticle stability, and the effect of nanoparticles on cell viability were evaluated. Further, inhibition tests were performed to demonstrate that the function of these novel nanoparticles is mediated via ER. RESULTS: Chitosan-raloxifene conjugate was successfully synthesized. The prepared nanoparticles showed sizes within 25–35 nm, more than 95% drug loading, about 60% of drug release and desired stability after 24 h. XTT assay on MCF-7 cell line illustrated that these nanoparticles could inhibit the cellular growth up to 60%. The results from inhibition tests revealed that prepared nanoparticles can inhibit cell growth via ER blocking. CONCLUSION: This study introduced chitosan-raloxifene nanoparticles containing doxorubicin as a novel targeting agent for adjuvant therapy of breast cancer. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40199-020-00338-9) contains supplementary material, which is available to authorized users.